Skeletal muscle mass, muscle strength, and physical performance in children and adolescents with obesity - Zembura, Marcela; Czepczor-Bernat, Kamila; Dolibog, Patrycja; Dolibog, Paweł T.; Matusik, Paweł (Frontiers in Endocrinology, 2023)
Sarcopenic obesity (SO) is defined as obesity with low skeletal muscle function and mass. The aim of this study was to evaluate the presence of sarcopenic obesity according to different diagnostic criteria and assess the elements of sarcopenia in children and adolescents with obesity. A total of 95 children and adolescents with obesity (diagnosed with the usage of International Obesity Task Force-IOTF criteria) in the mean age 12.7(+/-3) years participated in the study. Body composition was assessed with the usage of bioelectrical impedance- BIA (Tanita BC480MA) and dual- energy x-ray absorptiometry- DXA (Hologic). Fat mass (FM) and appendicular skeletal muscle mass (SMMa) were expressed as kilograms (kg) and percentage (%). Muscle to fat ratio (MFR) was defined as SMMa divided by FM. Dynamometer was used in order to measure grip strength. Six-minute walk test (6MWT) and timed up and go test (TUG) were used to assess physical performance. The presence of SO ranged from 6.32% to 97.89% depending on the criteria used to define sarcopenia. Children with sarcopenia defined as co-occurrence of low skeletal muscle mass % (SMM%) measured by DXA (≤9ndcentile) according to McCarthy et al. and weak handgrip strength (≤10th centile) according to Dodds et al. had significantly lower SMMa measured by both DXA and BIA, lower maximal handgrip strength and lower physical performance. Maximal handgrip was positively correlated with SMMa (in kg) and SMMa% derived from both DXA and BIA, and BIA-MFR. Maximal handgrip was negatively correlated with waist to height ratio (WHtR). Distance of 6MWT correlated positively with BIA measured SMMa% and BIA-MFR. 6MWT distance correlated negatively with BIA- FM% and body mass index (BMI) z-score. TUG was positively correlated with BIA-FM%, BMI z-score, WHtR and IOTF category and negatively correlated with BIA SMMa% and BIA-MFR. The presence of sarcopenia in our study varied depending on the diagnostic criteria used. This is one of the first studies evaluating muscle mass, muscle strength and physical performance in children and adolescents with obesity. The study highlighted the need for implementation of consensus statement regarding SO diagnostic criteria in children and adolescents.